1981
DOI: 10.1017/s0022172400069205
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies toEubacteriumandPeptostreptococcusspecies and the estimated probability of Crohn's disease

Abstract: Anaerobic coccoid rods belonging to species of Eubacterium and Peptostreptococcus agglutinate more frequently with sera from patients with Crohn's disease than with sera from patients suffering from other diseases and from healthy subjects. Results of agglutination test with four strains of coccoid anaerobes were used to estimate the probability that a patient suffers from Crohn's disease. The data on healthy subjects and patients with Crohn's disease were subjected to logistic discriminant analysis. With the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The strength of agglutination should be considered when the tests with four strains were used to obtain one combined result. This was achieved by using discriminant analysis to estimate the probability that a patient suffers from Crohn's disease ( Van de Merwe, Schmitz & Wensinck, 1981). In the present report, sera with agglutination reactions giving an a posteriori probability > 0 95 were considered positive.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The strength of agglutination should be considered when the tests with four strains were used to obtain one combined result. This was achieved by using discriminant analysis to estimate the probability that a patient suffers from Crohn's disease ( Van de Merwe, Schmitz & Wensinck, 1981). In the present report, sera with agglutination reactions giving an a posteriori probability > 0 95 were considered positive.…”
Section: Methodsmentioning
confidence: 98%
“…The agglutination of these strains by sera from healthy subjects and from patients with Crohn's and other diseases is reported here. The results have been used to estimate the probability that a patient suffers from Crohn's disease by means of an interpretation based on discriminant analysis (Van de Merwe, Schmitz & Wensinck, 1981). Subsequently, sera submitted for the establishment of the diagnosis of Crohn's disease have also been interpreted in this way.…”
Section: Introductionmentioning
confidence: 99%
“…Forty sera were assigned to one of four groups: group 1, CD with a positive agglutination reaction; group 2, CD with a negative agglutination reaction; group 3, not CD with a positive agglutination reaction; group 4, not CD with a negative agglutination reaction. The agglutina tion reaction was called positive when the posterior probability of CD (p value) calculated from the four agglutination reactions was 3= 0.80 and negative when the p value was < 0 .8 0 [3]. Reactions with a p s* 0.80 support the diagnosis CD.…”
Section: Methodsmentioning
confidence: 99%
“…The con centration of the PPC fraction in the feces of patients with CD was lower compared with that of HS [1], Other studies from our labo ratory showed that sera from patients with CD agglutinated strains of Coprococcus comes, Peptostreptococcus productus and Eubacterium contortum, present in the intesti nal anaerobic flora, more often and strongly than sera from patients with ulcerative coli tis, other diseases, and HS. The agglutina tion reactions are used as a diagnostic test for CD [2][3][4],In this study we investigated the bacterial origin of the soluble intestinal PPC and the occurrence of specific antibodies to PPC in sera from patients with CD and control HS. …”
mentioning
confidence: 99%
“…In Rotterdam, a much higher incidence of agglutinins to anaerobic bacteria of Eubacterium and Peptostreptococcus species was found in the sera of patients with Crohn's disease than in those from healthy controls (Wensinck, 1975 and1976;Van de Merwe, Schmitz and Wensinck, 1981;Wensinck and Van de Merwe, 1981). These workers also identified increased numbers of these bacteria in the stools of patients with the disease .…”
Section: Introductionmentioning
confidence: 96%